Laparoscopic myomectomy - Flint, Enrique (2015)
Leiomyomas are tumors with multifactorial origin and high prevalence, whose treatment is indicated when they originate disorders due to location and/or size. Myomectomy by laparoscopy is an excellent alternative with proper indication and correctly executed, after ample experience and evidence of advantageous results related to the conventional procedure in the short or long range, with respect rapid recuperation, less post operative pain and less adhesions formation, among others.